Ethical dilemmas in educational research considering challenges and risks in practice - Brown, Carol; Wild, Mary (Open University Press, 2023)
"Ethical Dilemmas in Educational Research is a valuable resource for both researchers and supervisors. Having myself sat on a university ethics committee, I appreciate not only the considerations needed when approving applications but also the controversy around what could be viewed as undue restrictions on research. The real-life and hypothetical dilemmas presented in this book should help guide researchers towards effective but ethically sensitive designs. This book not only provides useful information on the researcher's responsibilities regarding their participants, but also includes the importance of addressing their own wellbeing during the research process, something that is often overlooked."